TRANSLATION AND ADAPTATION OF THE “LUMBAR STIFFNESS DISABILITY INDEX” QUESTIONNAIRE INTO PORTUGUESE - Guarçoni Netto,Angelo (2019)
ABSTRACT Objective: To develop a version of the Lumbar Stiffness Disability Index (LSDI), translated into Portuguese and culturally adapted for the Brazilian population. Methods: The well-established process of translation into Portuguese and back translation into English was used together with cultural adaptation. Results: Five bilingual translators (English and Portuguese) performed the translation of the Lumbar Stiffness Disability Index (LSDI) from English to Portuguese based on interactive discussions used to arrive at a consensus translation. The translated version of LSDI was then translated into English by a native English-speaking translator who did not know the concepts involved in LSDI. The original LSDI and back translation were compared by a committee formed by the translators responsible for translating the original into Portuguese and a North-American spine surgeon, and because they were considered equivalent, the final version of the LSDI translated into Portuguese and culturally adapted was defined. Conclusions: In order to facilitate global and cross-cultural comparisons of the influence of lumbar stiffness related to spinal arthrodesis in daily activities, this study presents a version of LSDI that has been translated into Portuguese and culturally adapted for the Brazilian population. Level of Evidence; Not Applicable. Prospective Study.